(untitled) (World Economics and Finance Bulletin, 2025)
The question on the potential implications of the analysis of corporate proletarian dividend policies has been a particularly contentious issue in corporate finance and not just the field of corporate finance, since it also has ramifications about financial stability. This paper evaluated dividends, two variables proxied by the dividend payout ratio (DPR) and cash dividend payout (CDP), as dimensions of financial stability, as with profitability and ROA and ROE, liquidity and the current ratio (CR), leverage and the debt ratio (DRR), and the financial and indicator variables of the normalized cash from operational activity flows versus total assets and actual cash flow disclosure. three contributions to total asset methods at the district level, as three forms of the same cross-sectional data under fixed effects time models per corporation, had control variables for the corporate enterprise for variables for enterprise scale and measures for the dependability of the measure of financial stability to proxy total financial stability. The results demonstrate the significance of dividend policy related to financial health. The firms with dividends were more profitable, had higher liquidity ratios, a more favorable debt ratio and generally, cash flows with lower variability. The control variables lend confidence to the idea that firms with higher growth in sales and larger size were still able to maintain a healthy financial structure. The robustness tests include particularly the sub-sample estimation by firms’ size, other variations in the financial ratios, and the regime shifting tests for crisis periods. This research article contributes to the body of knowledge in the area, offering empirical evidence to the many theoretical models, including Bird-in-the-Hand, Agency, Signaling and Pecking Order just to name a few. In this sense, the findings demonstrate that dividend distribution should not be researched or considered on its own, or simplify it down to the transfer of wealth to shareholders, but a way to offer a financial QOL down the path. The findings of this study adds to the investor, regulators and managers understanding as to the dividend policies exposure to firm resilience and health of firms during periods of uncertainty.